PRELUDE FOR A SUCCESSFUL DIGITAL TRANSFORMATION: EMPIRICAL EVIDENCE FROM INDIAN TELECOMMUNICATION SERVICE PROVIDER - Dr. Jigna Srivastava`; Dr. Karippur Nanda Kumar; Dr. Anna Tarabasz (PEOPLE: International Journal of Social Sciences, 2024)
Despite an increased focus on digital transformation, the telecommunication industry has, thus far, seen limited success regarding the effective transformation of its constituent organisations, both globally and in India. Indian telecommunication service providers (TSP) in particular face tremendous pressure to transform successfully in order to leverage the benefits of digital transformation and meet the current business challenges. This research proposes factors from internal organizational perspective that are essential for the successful transformation. This study has developed a research framework grounded in multiple theories (Resource Based View, Dynamic Capabilities and Disruptive Innovation) and based on detailed literature review. The research model was tested using responses from a robust sample of 294 domain experts in the Indian telecommunications industry. Empirical results indicate that Digital Capabilities, Digital Strategy and Corporate Level Data Strategy has strong significance on the successful Business Performance, followed by IT Function Transformation, and Digital Innovation. Despite an increased focus on digital transformation, the telecommunication industry has, thus far, seen limited success regarding the effective transformation of its constituent organisations, both globally and in India. Indian telecommunication service providers (TSP) in particular face tremendous pressure to transform successfully in order to leverage the benefits of digital transformation and meet the current business challenges. This research proposes factors from internal organizational perspective that are essential for the successful transformation. This study has developed a research framework grounded in multiple theories (Resource Based View, Dynamic Capabilities and Disruptive Innovation) and based on detailed literature review. The research model was tested using responses from a robust sample of 294 domain experts in the Indian telecommunications industry. Empirical results indicate that Digital Capabilities, Digital Strategy and Corporate Level Data Strategy has strong significance on the successful Business Performance, followed by IT Function Transformation, and Digital Innovation.